2021
DOI: 10.7717/peerj.11615
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome analysis associated with polysaccharide synthesis and their antioxidant activity in Cyclocarya paliurus leaves of different developmental stages

Abstract: Background Cyclocarya paliurus (Batal.) Iljinskaja is a common endemic tree species and used as a Chinese medicine. The main active components in the leaves of this plant are polysaccharides. However, the temporal patterns of gene expression underlying the synthesis of polysaccharides in C. paliurus at different leaf developmental stages and its relationship with the polysaccharide content and antioxidant activities has not been reported to date. Methods RNA-seq was used to investigate the biosynthesis pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 57 publications
0
7
0
Order By: Relevance
“…It is characterized by four distinct seasons, abundant rainfall, no severe cold in winter, no intense heat in summer, early spring and long summer, warm and humid. On May 1, 2018, mature leaves with the largest leaf area at F4 stage ( Lin et al, 2020 , 2021 ; Sheng et al, 2021 ) were collected from C. paliurus plants growing at the two locations. The leaves collected from high altitude were significantly larger and longer than those collected from low altitude ( Supplementary Figure 1 and Supplementary Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…It is characterized by four distinct seasons, abundant rainfall, no severe cold in winter, no intense heat in summer, early spring and long summer, warm and humid. On May 1, 2018, mature leaves with the largest leaf area at F4 stage ( Lin et al, 2020 , 2021 ; Sheng et al, 2021 ) were collected from C. paliurus plants growing at the two locations. The leaves collected from high altitude were significantly larger and longer than those collected from low altitude ( Supplementary Figure 1 and Supplementary Table 2 ).…”
Section: Methodsmentioning
confidence: 99%
“…In the Spring of 2015, 1-year-old seedlings of C. paliurus were purchased from Yongfeng Town, Shuangfeng County, Hunan Province, China. Subsequently, the seedlings were transplanted on a field basement of Longquan at low altitude (E119 • 1 10 , N28 (Lin et al, 2020(Lin et al, , 2021Sheng et al, 2021) were collected from C. paliurus plants growing at the two locations. The leaves collected from high altitude were significantly larger and longer than those collected from low altitude (Supplementary Figure 1 and Supplementary Table 2).…”
Section: Plant Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have confirmed that the main polysaccharide compounds in C. paliurus have antioxidant activities. After using RNA-seq technology to study the polysaccharide synthesis pathway at different stages of leaf development and to detect the polysaccharide content and antioxidant activity, Liu et al found that the hydroxyl scavenging activity was the highest and the antioxidant capacity was the strongest in the first stage [ 55 ]. The health beverage composed of C. paliurus polysaccharides and Momordica saponin has been proven in the worm model to ameliorate oxidative damage by reducing the levels of ROS, MDA, and nonesterified fatty acids [ 56 ].…”
Section: Summary On Potential Mechanism Of C Paliurus On T2dm ( Figure 1 )mentioning
confidence: 99%
“…Previous studies also indicated that polysaccharides can act as compatible solutes and enhance abiotic stress tolerance, such as drought and salt stress in plants ( Yu et al, 2017 , 2021 ). In recent years, intermediate metabolites and genes related to polysaccharide biosynthesis have been explored in various plants, including Arabidopsis , wheat, rice, Cyclocarya paliurus , Cynomorium songaricum , Dendrobium officinale , and Polygonatum odoratum ( Northcote and Pickett-Heaps, 1966 ; Meng et al, 2009 ; Oh et al, 2013 ; Zhang et al, 2016 ; He et al, 2017 ; Zhang et al, 2020 ; Lin et al, 2021 ; Wang et al, 2021a ). Studies have discovered that polysaccharides are biosynthesized via continuous enzymatic reactions from sucrose, requiring invertase (INV), hexokinase (HK), fructokinase (scrK), mannose-6-phosphate isomerase (MPI), phosphomannomutase (PMM), mannose-1-phosphate guanylyltransferase (GMPP), GDP-mannose 4,6-dehydratase (GMDS), GDP-L-fucose synthase (TSTA3), UDP-glucose 4-epimerase (GALE), UDP-glucose 6-dehydrogenase (UGDH), UDP-apiose/xylose synthase (AXS), UDP-arabinose 4-epimerase (UXE), UDP-glucose 4,6-dehydratase (RHM), 3,5-epimerase/4-reductase (UER1), and glycosyltransferase (GT) ( Figure 2 ; Zhang et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%